Dendritic cells in IBD pathogenesis: an area of therapeutic opportunity?. Issue 2 (January 2014) - Bates, Jennifer; Diehl, Lauri
Abstract Dysfunction of the mucosal immune system plays an important role in inflammatory bowel disease (IBD) pathogenesis. Dendritic cells are emerging as central players based on both our increasing understanding of how genetic susceptibility impacts the mucosal immune system and the key role of dendritic cells in regulating response to gut microflora. We discuss areas of therapeutic opportunity in this evolving landscape. © 2013 The Authors. Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.